Generalized Modus Tollens with Linguistic Modifiers for Inverse Approximate Reasoning - Le Anh Phuong (International Journal of Computational Intelligence Systems, 2014)
Based on our previous researchs about generalized modus ponens (GMP) with linguistic modifiers for If … Then rules, this paper proposes new generalized modus tollens (GMT) inference rules with linguistic modifiers in linguistic many–valued logic framework with using hedge moving rules for inverse approximate reasoning.